Some New Results on Fixed Points of Meromorphic Functions Defined in Annuli. (17th December 2015) - Wu, Zhaojun; Xuan, Zuxing; Chen, Yuxian
Abstract : The purpose of this paper is to investigate the fixed points of meromorphic functions in annuli. Some well-known facts of fixed points for meromorphic functions in the plane will be considered in annuli.